Contribution of multidisciplinary healthcare professionals in the management of gestational diabetes mellitus: case study on selected hospitals in Dhaka - Modasser, Khadiza Binta (BRAC Univeristy, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2016.